Lambda production in 40 A GeV/c Pb-Au collisions - Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Drees, Axel; Esumi, ShinIchi; Filimonov, Kirill; Glässel, Peter; Milošević, Jovan; Petráček, Vojtech; Schmitz, Wolfgang; et al. (Journal of physics. G, Nuclear and particle physics, 2002)
During the 1999 lead run, CERES has measured hadron and electron-pair production at 40 A GeV/ c beam momentum with the spectrometer upgraded by the addition of a radial TPC. Here the analysis of Λ and ##IMG## [http://ej.iop.org/images/0954-3899/28/7/340/lamimg_1.gif] will be presented.